Hepatoprotective effect of chlorogenic acid against chronic liver injury in inflammatory rats. (November 2019) - Chen, Zhenlong; Yang, Yuhui; Mi, Shumei; Fan, Qingsheng; Sun, Xiaoming; Deng, Baichuan; Wu, Guoyao; Li, Yafei; Zhou, Quancheng; Ruan, Zheng
Graphical abstract: Note: Effect of chlorogenic acid (CGA) on liver and intestine in lipopolysaccharide-induced (LPS-induced) rat model. Highlights: Dietary chlorogenic acid have a hepatoprotective effect. Dietary chlorogenic acid improved micromorphology of liver and intestine. Chlorogenic acid affected liver mitochondrial energy metabolism and amino acid metabolism. Abstract: Chlorogenic acid (CGA) is a type of phenolic acid that has antioxidant and anti-inflammatory activities. In this study, we investigated the hepatoprotective effect of CGA in lipopolysaccharide (LPS)-treated rats. Supplementation with CGA attenuated ( P <  0.05) hepatocyte necrosis and inflammatory cell infiltration, decreased ( P <  0.05) the activities of serum transaminases and alkaline phosphatase and the level of total bilirubin, and increased ( P <  0.05) the level of serum total protein in comparison with the LPS-only group. In addition, CGA potently inhibited ( P <  0.05) the LPS-induced drop in the activities of mitochondrial NADH dehydrogenase and ATP synthase and the contents of ATP and AMP in the liver. Furthermore, CGA could partially counteract the changes induced by lipopolysaccharide in many metabolic pathways, such as energy metabolism, amino acid metabolism, and glutathione metabolism. In summary, our study showed that CGA supplementation had a protective effect against LPS-induced chronic liver injury.